2017
DOI: 10.1111/ffe.12738
|View full text |Cite
|
Sign up to set email alerts
|

Is the temperature plateau of a self‐heating test a robust parameter to investigate the fatigue limit of steels with thermography?

Abstract: A critical aspect of standard test methods for fatigue characterization is that they do not provide any information on heat dissipation in the material and involve very expensive experimental campaigns in time and costs. In recent years, thermographic methods capable of reducing testing time have been developed, also providing more information on damage occurring in the material. A commonly used approach is based on the assessment of the temperature plateau during a stepwise loading procedure. At times, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…In the fatigue crack growth tests, standard CT specimens were loaded on electrohydraulic machine and the crack length on the crack front was measured by a stereomicroscope [99]. To assess the location and the time of damage onset, thermographic methods have been used to achieve information about the damage [100][101][102][103][104]. Palumbo et al [105] monitored the AA5754-H111 specimens by infrared detector during experiment and the thermal signal is related to the energy dissipated in the material plastic deformation zones.…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…In the fatigue crack growth tests, standard CT specimens were loaded on electrohydraulic machine and the crack length on the crack front was measured by a stereomicroscope [99]. To assess the location and the time of damage onset, thermographic methods have been used to achieve information about the damage [100][101][102][103][104]. Palumbo et al [105] monitored the AA5754-H111 specimens by infrared detector during experiment and the thermal signal is related to the energy dissipated in the material plastic deformation zones.…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…Moreover, the evolution of plastic local deformation and strain distribution of DP steel has been researched considering the microstructure features [11][12][13][14]. In addition, the effects of the microstructures, ferrite content, and test temperature on the mechanical properties (i.e., tensile properties, fatigue behaviors, and crack propagation properties) of austenitic-ferrite duplex stainless steel were researched as well [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Different authors found that in presence of a dissipative phenomenon such as a crack, in a material undergoing a cyclic loading, it is possible to define the plastic volume which, dissipates energy around the crack [23][24][25].…”
Section: Theorymentioning
confidence: 99%
“…By considering a bilinear hysteresis loop where kinematic and isotropic hardening phenomena are neglected Figure 2, at stress ratio of R=-1, for sake of simplicity. Until the load is elastic, the behaviour of material is described by a full recovery of elastic energy per cycle and irreversible dissipative sources are zero [23]. The cyclic loading produces a delay between strain and stress involving the occurrence of the hysteresis loop.…”
Section: Theorymentioning
confidence: 99%